SEDIMENTARY EVOLUTION AND RELATED POLLUTION IN DONGNAI RIVER MOUTH AREA AND THIVAI TIDAL CHANNEL SYSTEM - Nghi, Tran; Thanh, Dinh Xuan; Mai, Dang; Thai, Nguyen Dinh; Nhan, Tran Thi Thanh; Thao, Hoang Thi Phuong (Vietnam Journal of Marine Science and Technology, 2008)
The geosystem of Dong Nai – Thi Vai river mouth consists of two types as follows. Soai Rap estuary and Thi Vai tidal channel system. Variablle history of this geosystem was closely connected to geological sedimentary evolution in Holocen, especially, in late Holocen, sea level change and modern tectonic movement. The delta plain Dong Nai was formed by late Holocen regressive phase from 3.000 years BP to 1.500 years BP. Modern ingressive has been a principal reason of destroying this delta in relation to sedimentary lack and subsided tectonic movement. These processes have changed lith ofacies landscap from deltaic facies to tidal channel system in which, the sandy silt-clay deltaic facies have become silt-silt clay tidal channel facies and mangrove clay marshy facies. Varied relief of bottom of Thi Vai tidal channel was caused by erosion of tidal currents led to form semi-izolate basin from open sea by semi diurnal regime. That’s why, hydrothithodynamic mechanism was a basic cause of pollution accumulation in the water and bed sediments